Health-Related Quality of Life in Children With Congenital Hyperinsulinism - Männistö, Jonna M. E.; Jääskeläinen, Jarmo; Huopio, Hanna (Frontiers in Endocrinology, 2019)
Background Quality of life (QoL) has not been studied in patients with congenital hyperinsulinism (CHI). Objectives To examine whether the health-related quality of life (HRQoL) is worsened in patients with persistent or transient CHI. Methods We studied HRQoL of 65 children with CHI aged 3-17 years (60% males) recruited from the nationwide CHI registry. The median ages were 9.6 (range 3.5-16.3) and 7.4 (3.1-17.9) years in persistent (P-CHI, n = 33) and transient (T-CHI, n = 32) CHI groups, respectively. HRQoL was examined by generic KINDL-R questionnaire and the scores were compared to the age- and gender-specific reference values. Results In self-reports of subjects aged 11 to 17 years and in parent reports of children aged 3 to 17 years, P-CHI or T-CHI children did not have statistically lower scores in any of the six dimensions (physical well-being, emotional well-being, self-esteem, family, friends, and school) or in total scores compared to the reference values. Conclusions Congenital hyperinsulinism is not associated with low HRQoL in childhood or adolescence.